Swirling pipeflow of non-Newtonian and particle-laden fluids - Tonkin, Ruth Julie Jane (2005)
This thesis describes the application of novel swirl inducing pipe to various pipe configurations, when pumping a range of fluids and fluid / particle mixtures. An extensive experimental programme, incorporating particle image velocimetry and photography, was implemented using a pipe flow loop designed specifically for the purpose.